A Frame-Semantic of the Verb ‘Fall down’ and the Verbs Related to the Cause of Fall down in Sundanese Language - Aan Ramadhansyah Rahayu (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2020)
This study shows how the theory of Frame Semantic developed by Fillmore & Baker (2010) can help to describe and analyze different kinds of frame elements of Sundanese verb evoking the ‘fall down’ frame. Many ways can be found in Sundanese verbs for evoking ‘fall down’ frame due to their variation in frame elements. This study applied a descriptive qualitative method, and the data are ten Sundanese lexis that evokes the frame ‘fall down’ collected as the unit of analysis. The main findings show that Sundanese verb, which evokes the ‘fall down’ have different frame elements. These differences of frame elements, including the part of the body, which fall down, the cause of falling and the direction of falling. Therefore, the detail frame elements in describing how the verb in Sundanese evokes the frame ‘fall down’ enrich the Sundanese vocabularies, which evoke the ‘fall down’ frame. Keywords: frame, frame elements, frame semantic